2020
DOI: 10.7759/cureus.11290
|View full text |Cite
|
Sign up to set email alerts
|

1,2 Intercompartmental Supraretinacular Artery-Based Vascularized Graft for Scaphoid Nonunion With Avascular Necrosis

Abstract: Background The treatment for scaphoid nonunion with avascular necrosis is vascularized and non-vascularized bone grafts. A vascularized bone graft promotes biological healing and revascularizes ischemic bone. The purpose of this retrospective study is to analyze the outcome of 1,2 intercompartmental supraretinacular artery (1,2-ICSRA)-based vascularized graft in scaphoid nonunion with avascular necrosis. Materials and methods We treated 11 patients with scaphoid nonunion with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Ten studies reported union rates for patients with proximal pole fractures exclusively with AVN (n = 225). 17,26,39,47,61,62,71,77,83,86 The union rate reported for these cases was 77.6% (95% CI 59.2 to 95.9) and vascularized grafts were used in all cases. One study used a medial femoral condyle graft, and the remaining studies employed grafts from the distal radius.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Ten studies reported union rates for patients with proximal pole fractures exclusively with AVN (n = 225). 17,26,39,47,61,62,71,77,83,86 The union rate reported for these cases was 77.6% (95% CI 59.2 to 95.9) and vascularized grafts were used in all cases. One study used a medial femoral condyle graft, and the remaining studies employed grafts from the distal radius.…”
Section: Resultsmentioning
confidence: 90%
“…There were 13 studies (298 patients) reporting outcomes for patients with AVN, nine of which reported outcomes for AVN only in proximal pole fractures, 17,26,39,47,61,62,71,83,86 while three had a heterogenous range of fracture sites (featuring 36.7% to 73.3% proximal pole fractures), 19,50,82 and one study reported dichotomized outcomes for AVN which involved proximal pole of the scaphoid and those which did not. 77 AVN was variably determined, both by visual appearance at surgery and/or preoperative MRI imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The proximal scaphoid is at risk of avascular necrosis after fracture, further limiting the potential recovery (Papatheodorou et al, 2021). Several surgical procedures have been developed to try to improve bone union, including various bone grafts (Borges et al, 2020; Jerome et al, 2020; Kim et al, 2018; Pulos et al, 2018). Union rates with traditional bone grafts used for proximal scaphoid nonunion have been reported to be between 64% and 74% (Krimmer, 2002; Morris et al, 2018).…”
Section: Introductionmentioning
confidence: 99%